A new species of mole cricket (Orthoptera: Gryllotalpidae: Gryllotalpinae) from Bukit Fraser, Malay Peninsula, with taxa notes on another similar mole cricket - Tan, Ming Kai; Kamaruddin, Khairul Nizam (Zootaxa, 2013)
One new species of Gryllotalpa from Bukit Fraser, Pahang of Malay Peninsula is described: Gryllotalpa fraser sp. n. Photographs of Gryllotalpa hirsuta Burmeister, 1838 were examined and some remarks are made here, including a comparison with Gryllotalpa fraser sp. n. and Gryllotalpa nymphicus Tan, 2012.